Modification of risk, but not survival of esophageal cancer patients by esophageal cancer‐related gene 1 Arg290Gln polymorphism: A case–control study and meta‐analysis. Issue 11 (22nd October 2013) - Umar, Meenakshi; Upadhyay, Rohit; Kumar, Shaleen; Ghoshal, Uday Chand; Mittal, Balraj
Abstract: Background and Aim: Esophageal cancer‐related gene 1 ( ECRG1 ) is a novel tumor suppressor gene known to affect matrix remodeling, cell growth, and differentiation. Previous studies in high incidence geographical regions of esophageal cancer (EC) have shown association of ECRG1 Arg290Gln polymorphism with risk of esophageal squamous cell carcinoma (ESCC); however, role of this variant in low incidence region is missing. So, we aimed to evaluate association of ECRG1 Arg290Gln with susceptibility and prognosis of EC patients in low‐risk north Indian population. Methods: The genotyping of ECRG1 Arg290Gln polymorphism was done in 310 incident EC cases (including 179 follow up cases) and 310 healthy controls through polymerase chain reaction‐restriction fragment length polymorphism. Statistical analysis applied were binary logistic regression for risk estimation and Kaplan–Meier/log‐rank test for survival analysis. Meta‐analysis of published studies, exploring role of ECRG1 polymorphism in ESCC risk, was carried out using MIX 2.0 software. Results: ECRG1 Arg290Gln polymorphism significantly conferred 1.8‐fold increased risk of EC in dominant model (odds ratio = 1.78, 95% confidence interval = 1.27–2.49, P = 0.001). Stratification based on clinical phenotypes showed pronounced risk in cases with ESCC histopathology and middle/lower third tumor locations. No significant interaction with environmental risk factors was observed. Meta‐analysis also showed significant association of ECRG1 Arg290Gln polymorphism with risk of ESCC. Kaplan–Meier and Cox regression tests suggested that ECRG1 polymorphism did not modulate survival outcome of ESCC patients. Conclusions: ECRG1 Arg290Gln polymorphism significantly affects the susceptibility but not the prognosis of ESCC patients in low‐risk north Indian population.